The Use of Wordwall Media to Improve Islamic Education Learning Outcomes at Imama Kedungpane Islamic Elementary School, Semarang City - Kahfi, Nazih Sadatul; Aula, Iqbal Ahsanul; Husni, Muhammad Wazid; Rokhani, Rokhani; Hakim, M. Abdul Rahman (Proceeding International Conference on Religion, Science and Education, 2025)
This study aims to determine how to establish a favorable learning environment and attain the best possible outcomes. To do this, educators must understand the significance of this and be able to modify their teaching methods. Using learning materials that are efficient, engaging, enjoyable, and significant for students is one of the innovative approaches to education. This study looks at how utilizing Wordwall as a teaching tool affects elementary school students' learning outcomes The quasi-experimental design with post-test-only control group design is the methodology employed in this study. The 46 participants in the study were all fifth-grade pupils at SD Islam Imama Kedungpane. With a total sample size of 28 students for the experimental group and another 28 for the control group, saturation sampling was the sampling method employed in this investigation. Data was gathered using a post-test with multiple-choice exam questions. The findings demonstrated that using Wordwall learning resources was superior to traditional learning methods that did not employ learning resources. Thus, it can be concluded that the use of Wordwall learning media has a positive effect on the learning outcomes of grade V students at SD Islam Imama Kedungpane, Semarang City